Fuzzy logic based selective harmonic elimination for single phase inverters - Duranay, Zeynep Bala; Guldemir, Hanifi (ASTES Publishers, 2018)
A selective harmonic elimination system using fuzzy logic for the elimination of high magnitude harmonics with frequencies close to fundamental in the output voltage of single phase inverters is presented. The system does not require look up tables for storage of the data as in traditional harmonic elimination methods. The input of the fuzzy system is the modulation index values. The output of the fuzzy system provides the switching angles which are further used to construct the switching signal for the switches in the inverter. With this fuzzy logic based selective harmonic elimination system, predetermined dominant low rank harmonics are successfully eliminated. Simulations are made with Matlab/Simulink and the results are presented which show the effectiveness of the presented harmonic elimination system. © 2018 Advances in Science, Technology and Engineering Systems.All right reserved.
Keywords: Fuzzy logic; Harmonic analysis; Harmonic elimination; Inverter; Pulse width modulation